We the women, we the subjects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The economic role of women in agricultural and rural development: promoting of income-generating activities. CTA. 2000. 64 pp. ISBN 92 9081 2249 CTA number 994. 10 credit points